2019
DOI: 10.1111/epi.16318
|View full text |Cite
|
Sign up to set email alerts
|

Operative posterior disconnection in epilepsy surgery: Experience with 29 patients

Abstract: Objective It has been suggested that multilobar epilepsies caused by lesions restricted to the posterior cerebral quadrant (ie, the parietal, temporal, and occipital lobes) can be treated successfully by a procedure termed posterior disconnection. The objective of the present paper was to identify determinants of the epileptological outcome following posterior disconnection surgery. Methods The authors retrospectively analyzed a series of 29 consecutive patients undergoing posterior disconnection surgery betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 33 publications
0
27
0
2
Order By: Relevance
“…At the later stages of the procedure, while performing the medial temporo-pareito-occipital disconnection, neuronavigation helps orient the disconnection in relation to falx as the location of falx does not change much with the brain shift. Kalbhenn et al [7] utilized cortical motor-evoked potential monitoring and a combined mapping and suction device for continuous subcortical direct stimulation to identify the motor pathways during surgery. It is imperative to utilize these adjuncts, so that the risk of hemiplegia is minimized following PQD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the later stages of the procedure, while performing the medial temporo-pareito-occipital disconnection, neuronavigation helps orient the disconnection in relation to falx as the location of falx does not change much with the brain shift. Kalbhenn et al [7] utilized cortical motor-evoked potential monitoring and a combined mapping and suction device for continuous subcortical direct stimulation to identify the motor pathways during surgery. It is imperative to utilize these adjuncts, so that the risk of hemiplegia is minimized following PQD.…”
Section: Discussionmentioning
confidence: 99%
“…However, very few studies have reported on the outcomes of posterior quadrant disconnection (PQD), a procedure utilized in conditions where the seizure focus is identified in the posterior head region. Kalbhenn et al [7] commented in 2019 that the literature contained only 6 reports describing ≥10 patients who underwent posterior disconnection surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Wurden früher für hauptsächlich große TPO-Mehrlappen Resektionen durchgeführt [14], haben sich in den letzten Jahren minimal-invasive Diskonnektionen durchgesetzt [15][16][17][18] Diese Entwicklung ist mit der Umstellung der Hemisphärektomie (Entfernung der Hemisphäre bis auf die Stammganglien) in Richtung Hemisphärotomie (nur Diskonnektion der Hemisphäre) bei Hemisphärenpathologien mit therapierefraktärer multifokaler unilateraler Epilepsie vergleichbar [19,20].…”
Section: Posteriore Resektion/ Diskonnektionunclassified
“…Diese gute Erfolgsrate konnte in einer retrospektiven Serie aus dem Klinikum Bethel (Kalbhenn et al 2019) an Patienten mit reiner TPO-Epilepsie bestätigt werden (84,6 % ILAE 1-Outcome) [16]. Dabei handelte es sich auch größtenteils um Kinder.…”
Section: Posteriore Resektion/ Diskonnektionunclassified
“…Current disconnection surgeries for DRE include functional hemispheric disconnection, corpus callosotomy, temporal disconnection, and posterior quadrant disconnection. Posterior quadrant disconnection was reported in few clinical series 10,14‐20 . We have come across only two surgical series in the literature involving temporal disconnection 11,21 .…”
Section: Introductionmentioning
confidence: 99%